0553 Upper Airway Stimulation:Titration Beyond the Attended Polysomnography. (12th April 2019) - Chuan Liu, Stanley Yung; poomkonsarn, sasikarn; Chou, Courtney; During, Emmanuel
Abstract: Introduction: The current protocol for patients after undergoing upper airway surgery (UAS) for obstructive sleep apnea (OSA) involves activation in clinic 1 month after the procedure, and titration in the sleep lab 2 months after the procedure. Some patients are intolerant of settings obtained from the titration study for optimal reduction of the apnea-hypopnea index (AHI). We describe a case series where these patients were titrated again under drug induced sleep endoscopy (DISE) to fine tune the amplitude and polarity of stimulation. Methods: 22 patients who underwent UAS (Inspire, Minnesota, USA) were included in this retrospective review. The mean age was 66.7± 8 years; male: female 20:2. Mean reduction in AHI was 36.4 to 4.3. Peri-operative attended polysomnography were obtained. Patients who felt intolerant of their device settings after 3 to 5 months of UAS trial were titrated anatomically via in-office endoscopy or drug-induced sleep endoscopy (DISE). Factors contributing to their intolerance were recorded. Results: 5 patients were uncomfortable with the device settings obtained for optimal control of the apnea-hypopnea index (AHI). Male: Female 3:2. Mean reduction in AHI was 32.64 to 5.7. Co-morbidity included: 1) 1 cardiovascular disease, 2) 1 hypertension, 3) 1 pulmonary disease, 4) 1 diabetes mellitus, and 5) 1 acquired immune deficiency syndrome. Under DISE (3 subjects), mouth breathing was a common finding. With mouth closure during DISE, the voltage could all be decreased to the lowest therapeutic range with effective tongue protrusion and airway opening. Another 2 subjects that required in-office titration presented with a history of stroke and acquired immunity deficit syndrome. Changing the polarity allowed proper activation of the tongue. Conclusion: It would be too simplistic to assume that all patients can be titrated adequately during attended polysomnography post-UAS. Patient related factors such as relevant co-morbidity, body position during sleep, and nasal versus oral breathing require continued collaboration between sleep medicine and surgery to optimize the efficacy and adherence of UAS. Future research should identify patients who are more likely to require both modes of titration to further elucidate ideal responders to UAS. Support (If Any): None